2015
DOI: 10.1177/0363546515585123
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Acute Groin Injuries

Abstract: Adductor injuries account for the majority of acute groin injuries. Iliopsoas and proximal rectus femoris injuries are also common. More than 1 in 5 injuries showed no imaging signs of an acute injury. Clinically diagnosed adductor injuries were often confirmed on imaging, whereas iliopsoas and rectus femoris injuries showed a different radiological injury location in more than one-third of the cases. The discrepancy between clinical and radiological findings should be considered when diagnosing acute groin in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(47 citation statements)
references
References 72 publications
1
43
0
3
Order By: Relevance
“…8 Understanding the physical requirements of each sport can help one appreciate the importance of maintaining a high adductor to abductor strength ratio. In a recent prospective study involving 110 athletes in various sports, Serner et al 9 found that kicking was the most common mechanism for acute groin injuries in soccer. The adductor longus was the most frequently injured muscle, and 81% of injuries involved the kicking leg.…”
Section: Implications For Practice Education and Future Researchmentioning
confidence: 99%
“…8 Understanding the physical requirements of each sport can help one appreciate the importance of maintaining a high adductor to abductor strength ratio. In a recent prospective study involving 110 athletes in various sports, Serner et al 9 found that kicking was the most common mechanism for acute groin injuries in soccer. The adductor longus was the most frequently injured muscle, and 81% of injuries involved the kicking leg.…”
Section: Implications For Practice Education and Future Researchmentioning
confidence: 99%
“…The adductor tendons are frequently involved in core injuries. 27 Adductor longus tendinosis is a result of chronic repetitive overuse and occurs immediately distal to the rectus abdominis–adductor longus aponeurosis. MRI findings include thickening with or without hyperintense signal, particularly on the fluid-sensitive sequence, distal to the rectus abdominis–adductor longus aponeurosis and with or without hypointense foci of calcification ( Figure 4 ).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Im Fußball hängen 40 % aller akuten Leistenverletzungen mit dem Ballschuss zusammen [9]. Bei einem sauber ausgeführten Schuss findet normalerweise ein effizienter Energiefluss zwischen den verschiedenen Segmenten statt, durch den eine Überlastung der Muskeln verhindert wird [39].…”
Section: Verletzungsmechanismusunclassified
“…Vor allem sollte die körperliche Untersuchung gut strukturiert und durchdacht sein, da Leistenschmerzen eine schwerwiegende Pathologie zugrunde liegen kann und zahlreiche muskuloskeletale Strukturen beteiligt sein können. Auf den ersten Blick scheint dies im Widerspruch zu der Tatsache zu stehen, dass es nicht möglich zu sein scheint, eine zuverlässige und fundierte anatomische Diagnose zu erstellen [9,10]. Daher wurde vorgeschlagen, einen umfassenden Ansatz zu verfolgen, um zwischen klinischen Entitäten zu differenzieren [11,12,13].…”
Section: Introductionunclassified